Reconstructing Paleo-oxygenation for the Last 54,000 Years in the Gulf of Alaska Using Cross-validated Benthic Foraminiferal and Geochemical Records - Sharon; Belanger, Christina; Du, Jianghui; Mix, Alan (Paleoceanography and Paleoclimatology, 2021)
Holocene and Pleistocene marine sediment records in the North Pacific record multiple dysoxic events proximal to continental margins and oxygen minimum zones (OMZs). High-resolution paleoenvironmental studies in the Gulf of Alaska (GoA) were previously restricted to the last ∼17,000 years, limiting our knowledge of oxygenation in the high latitude North Pacific. Here we develop a ∼54,000-year-long record of co-registered benthic foraminiferal assemblages and redox sensitive metal concentrations (Mo/Al and U/Al) at Site U1419 in the upper OMZ of GoA to reconstruct the history of OMZ extent and intensity at multi-centennial resolution. Using multivariate analyses of total benthic foraminiferal assemblages, we develop quantitative dissolved oxygen estimates that are robust to differences in the benthic foraminiferal size fraction analyzed, replicate modern oxygenation patterns in the GoA, and are cross-validated by redox sensitive metal concentrations. We identify dysoxic events in the early Holocene and in the Bølling-Allerød (B/A), consistent with previous studies, as well as two dysoxic events during MIS 3 that are comparable in severity to the B/A event and lower in oxygen than the modern GoA OMZ. We further record short-duration (<300 years) dysoxic events during glacial times similar to those recorded at more southern latitudes. Rates of oxygenation change can be abrupt with transitions exceeding 1 ml/L O2 in 100 years. Quantitative estimates of paleo-oxygenation, such as those possible with benthic foraminiferal assemblages, are important for forecasting future oxygenation changes in OMZs and their potential impacts on the marine ecosystems.
Keywords: abrupt change; Benthic foraminifera; Dysoxia; Hypoxia; North Pacific; redox sensitive metals